Towards a sustainable management plan for Iloilo River a resource use analysis - Devera, Cynthia Donasco (Miagao, Iloilo University of the Philippines in the Visayas, 2002)
The study was conducted to determine the present status and use of Iloilo River. The issues and concerns affecting its sustainable use were also identified in this study. Primary and secondary data were collected in the study. Interview was done with 29 respondents in 5 pre-selected barangays along the river using a questionnaire. The respondents were the barangay captains, kagawads, SK members, fisherfolks, teachers (day care and elementary school) and sari-sari store owners. Iloilo River is used as port for inter-island cargo and passenger vessels, fishing grounds for sustenance fishermen and source of water for fishponds and salt making. The river is also the recipient of effluents from commercial establishments and households along the river and its tributaries. The water quality of Iloilo river is classified under the Class "C" category but collated primary and secondary dat ashowed that the river's productivity is declining and its condition is deteriorating due to effluents discharged to the river.Aside from the threats of pollution, issues on increasing population, enforcement of environmental laws and regulated use of the river are believed to affect its condition. To address the various issues and concerns confronting the river's condition., the city government should formulate a management plan for the river. This plan could have a water monitoring system, information, campaigns to raise environmental consciousness and regulation of activities in the river. The managment plan should be supported by the community to ensure its sustained implementation.
Special Problem (MMA) -- Miagao, Iloilo : University of the Philippines in the Visayas, 2002.